2012
DOI: 10.18632/aging.100521
|View full text |Cite
|
Sign up to set email alerts
|

Potential anti-aging agents suppress the level of constitutive mTOR- and DNA damage- signaling

Abstract: Two different mechanisms are considered to be the primary cause of aging. Cumulative DNA damage caused by reactive oxygen species (ROS), the by-products of oxidative phosphorylation, is one of these mechanisms (ROS concept). Constitutive stimulation of mitogen- and nutrient-sensing mTOR/S6 signaling is the second mechanism (TOR concept). The flow- and laser scanning- cytometric methods were developed to measure the level of the constitutive DNA damage/ROS- as well as of mTOR/S6- signaling in individual cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
84
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 73 publications
2
84
0
Order By: Relevance
“…Halicka et al have shown that gerosuppressive agents, including rapamycin, reduced the level of expression of gH2AX, in various cell types. 49 It is of interest to examine if RAD50 is involved in this decreased expression of gH2AX. DNA damages are able to decelerate, and even arrest, cell cycle so that they can be repaired.…”
Section: Discussionmentioning
confidence: 99%
“…Halicka et al have shown that gerosuppressive agents, including rapamycin, reduced the level of expression of gH2AX, in various cell types. 49 It is of interest to examine if RAD50 is involved in this decreased expression of gH2AX. DNA damages are able to decelerate, and even arrest, cell cycle so that they can be repaired.…”
Section: Discussionmentioning
confidence: 99%
“…), hormones (GH, thyroid hormones, adrenal and sexual hormones, melatonin [50]), bioregulatory peptides (timalin, epithalmin), biguanides (metformin, fenformin) [77], adaptogens (ginseng [48]). Sirolimus or rapamycin, described as immunosuppressive and antitumoral drug has been shown to be also an anti-ageing drug [41] whose goal is the TOR gene in yeast [43] and mTOR gene, its mammalian correspondent, also known as FK506 factor or FRAP1, a serine/threonine kinase that regulates cell growth, viability, mobility, protein synthesis and gene transcription [31,45,78]. Rapamycin, according to recent studies, may act preventively in atherosclerosis, hypertonia and hypercoagulation, thus preventing myocardial infarction, cardiovascular accidents, osteoporosis, cancer, autoimmune diseases, arthritis, fat diabetes, Alzheimer and Parkinson diseases [31,42,45].…”
Section: Geroprotectors Geroprotectors Geroprotectors Geroprotectorsmentioning
confidence: 99%
“…2 deoxyglucose [78] is a glucose analog that absorbed by cells determine glucose inhibition resulting in decreased cellular energetic metabolism, situation that mimics calorie restriction. Data concerning the geroprotectection of this substance is not yet relevant.…”
Section: Geroprotectors Geroprotectors Geroprotectors Geroprotectorsmentioning
confidence: 99%
“…[62][63][64][65][66][67][68][69][70] In the organism, suppression of geroconversion prevents age-related diseases in mammals [70][71][72][73][74][75][76][77][78] and pathological conditions in invertebrates, 79,80 extending healthy lifespan.…”
mentioning
confidence: 99%